Implementing the Competencies Compound Inventory for 21st Century Competencies in Brazil: implications for research and practice - Roberson, Nathan Dale; Pereira, Thaiane; Horvathova, Michaela (Frontiers in Education, 2025)
As education systems evolve to meet the demands of the 21st century, there is a growing recognition that students must develop not only academic knowledge but also a broad set of competencies, including social–emotional skills, character, and meta-learning. To support this shift, educators require reliable and scalable tools to assess and guide student development in these areas. This study examines the translation and validation of the Competencies Compound Inventory for the 21st Century (CCI-21) into Brazilian Portuguese (CCI-21-P), a tool designed to measure 12 key competencies aligned with the 4-Dimensional Education model and Brazil’s national education framework, the BNCC (Base Nacional Comum Curricular). Using data from 60,791 upper primary and secondary students across more than 450 cities in Brazil, we evaluated the psychometric properties of the CCI-21-P through analyses of item sensitivity, reliability, and internal structure. Results indicate strong internal consistency (α = 0.92) and a factor structure largely comparable to the original English version, supporting the instrument’s validity and cultural adaptability. Findings suggest that the CCI-21-P is a reliable and practical tool for assessing 21st Century Competencies in Brazilian schools. Its use enables educators to align competency development with national curriculum goals while contributing to international efforts to benchmark social–emotional learning (SEL) measurements across diverse contexts. Continued validation and adaptation will further strengthen its utility in informing policies and practices regarding holistic education.